Gambaran Tingkat Kemandirian Lansia dalam Pemenuhan ADL (Activity Daily Living) - Ratna Wulandari (STIKes Patria Husada Blitar, 2014)
The influence of the aging process can a variety of problems both physically, mentally and economically so as to affect the fulfillment of the ADL (Activity Daily Living). The level of ability of the elderly in activity can be measured by the level of independence of elderly in performing 6 basic activities include bathing, dressing, toileting, moving, continence and eating.. Method: The research design was description design. The population was 80 elders in UPT PSLU Blitar, the sample was 44 by purposive sampling technique. Data were collected byÂ interviews guided. Result : The results showed that 86.4% 6 independent activities, 11.4% 5 activities, and 2.3% 4 activities. Elderly that has a high level of independence is has physical and psychological health and sufficient prima. Discussion : By getting a good health the elderly can perform any activity in their everyday lives. It is expected that the results of this study, carers must keep the safety of elders in activities to prevent deterioration in elderly activities which could be due to fall or hurt.